ANALISIS PENERAPAN AKUNTANSI LINGKUNGAN SEBAGAI PERTANGGUNGJAWABAN SOSIAL DI RUMAH SAKIT UMUM DAERAH S.K. LERIK KOTA KUPANG - Dau, Yuliana Benedikta (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2023)
This research aims to determine the application of environmental accounting as social responsibility at the S.K Lerik General Hospital and determine the efforts made by the hospital to reduce the environmental impact caused by hospital operational activities and to find out what costs have been reported by the hospital. . This research uses a qualitative approach, descriptive research type. Research informants were finance staff, sanitation staff, visitors/patients and the community who were determined based on purposive sampling techniques. The research was carried out in four stages, namely: data collection, data reduction, data presentation and conclusions. The results of the research concluded that the S.K Lerik Kupang Regional General Hospital had carried out the accounting treatment stages for waste management costs and recognized environmental costs incurred as operational costs, this recognition used the accrual basis method. Hospitals measure costs in terms of waste management based on the acquisition price in the previous year or budget (Historical Cost). Reporting environmental costs together into one financial report. Costs are included in the operational costs item. The S.K Lerik Kupang Regional General Hospital has managed its waste well, waste in the hospital is divided into two, namely liquid waste and solid waste, liquid waste is managed with an IPAL machine using the an-aerobic BIO FILTER system and solid waste is managed with an incinerator machine.